2023
DOI: 10.1302/0301-620x.105b4.bjj-2022-0628.r1
|View full text |Cite
|
Sign up to set email alerts
|

Absolute synovial polymorphonuclear neutrophil cell count as a biomarker of periprosthetic joint infection

Abstract: AimsThe aim of this study was to evaluate the diagnostic accuracy of the absolute synovial polymorphonuclear neutrophil cell (PMN) count for the diagnosis or exclusion of periprosthetic joint infection (PJI) after total hip (THA) or knee arthroplasty (TKA).MethodsIn this retrospective cohort study, 147 consecutive patients with acute or chronic complaints following THA and TKA were included. Diagnosis of PJI was established based on the 2018 International Consensus Meeting criteria. A total of 39 patients diag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…As noted above, PJI was diagnosed based on the International Consensus Meeting 2018 criteria [33] through preoperative assessment of serum (C-reactive protein, erythrocyte sedimentation rate, and D-dimer) and synovial parameters (white blood cell count, polymorphonuclear neutrophil count, alpha-defensin, and microbiological analysis) [16]. Furthermore, tissue samples for histologic and microbiologic analysis were obtained during revision surgery in all patients from the bone-prosthesis interface.…”
Section: Methodsmentioning
confidence: 99%
“…As noted above, PJI was diagnosed based on the International Consensus Meeting 2018 criteria [33] through preoperative assessment of serum (C-reactive protein, erythrocyte sedimentation rate, and D-dimer) and synovial parameters (white blood cell count, polymorphonuclear neutrophil count, alpha-defensin, and microbiological analysis) [16]. Furthermore, tissue samples for histologic and microbiologic analysis were obtained during revision surgery in all patients from the bone-prosthesis interface.…”
Section: Methodsmentioning
confidence: 99%
“…Synovial fluid obtained with a hip aspirate should be sent for differential cell analysis and both aerobic and anaerobic cultures. A white cell count of 2,000–3,600 and a differential of >80% polymorphnuclear (PMN) leukocytes is suspicious for infection ( 11 , 12 ). Jandl et al ( 12 ) demonstrated an absolute PMN cell count of less than 2,000/µL as adequate for ruling out periprosthetic joint infection.…”
Section: Pre-operative Planningmentioning
confidence: 99%
“…A white cell count of 2,000–3,600 and a differential of >80% polymorphnuclear (PMN) leukocytes is suspicious for infection ( 11 , 12 ). Jandl et al ( 12 ) demonstrated an absolute PMN cell count of less than 2,000/µL as adequate for ruling out periprosthetic joint infection. In the presence of metal-on-metal components, or an adverse reaction to metal debris in metal on polyethylene implants, metal ions including cobalt and chrome should also be tested.…”
Section: Pre-operative Planningmentioning
confidence: 99%